14 - Conference on International Criminal Justice, Reconciliation and Peace in Africa: The ICC and Beyond - Wamai, Njoki (CODESRIA Bulletin, 2021)
From 10-12 July 2014 , CODESRIA, in collaboration with the Social Science Research Council and the Centre for Democracy and Development in West Africa, Abuja, Nigeria, organised an international conference on “International Criminal Justice, Reconciliation and Peace in Africa”. The conference, which was held in Dakar, was opened bySenegal’s Minister of Justice, Hon. Sidiki Kaba. It brought together around one hundred researchers and practitioners including representatives of the ICC, the African Court on Human and Peoples Rights, and the International Criminal Tribunal for Rwanda for discussions on a range of issues touching on redress for mass atrocities and the worst human rights abuses as well as the way toward building reconciliation and sustained peace in African countries. Below is the conference report.